2007
DOI: 10.1177/039463200702000115
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Clinical Response in Allergic Rhinitis Patients Treated with an Oral Immunostimulating Bacterial Lysate: In Vivo Immunological Effects

Abstract: Allergic rhinitis is known to be one of the most common chronic diseases in the industrialized world. According to the concept that allergic rhinitis patients generally suffer from an immune deficit, in order to stimulate specifically or aspecifically their immune system, immunomodulating agents from various sources, such as synthetic compounds, tissue extracts or a mixture of bacterial extracts, have been used. The aim of the present trial is to evaluate the efficacy of the treatment with an immunostimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…BV was able to shift Th1/Th2 polarization in patients with allergic rhinitis [20]. Asthma and allergic rhinitis cause similar immunological changes.…”
Section: Discussionmentioning
confidence: 99%
“…BV was able to shift Th1/Th2 polarization in patients with allergic rhinitis [20]. Asthma and allergic rhinitis cause similar immunological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptides control the huge number of incoming and outgoing signals, which take place in the hypothalamus, since they are basically the carriers of these signal data (30)(31)(32)(33). The sense of appetite is probably due partly to Orexin A, and partly to the existence of a whole group of neuropeptides acting together in the hypothalamus and the gastrointestinal tract (1-2, 34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in children and adults suffering from repeated upper respiratory tract infections, and it efficiently reduces both the frequency and the duration of the infections [10]. Some studies have recently shown that BV can induce Treg in vitro and in vivo that confers protection against asthma [11], [12]. However, the mechanisms by which Treg responses are stimulated by bacterial extracts remains unclear.…”
Section: Introductionmentioning
confidence: 99%